Ragam Bahasa Pada Caption Instagram: Analisis Gender (Variety of Languages on Instagram Captions: Gender Analysis) - Adinda Oktaseska Agata; Aceng Ruhendi Saifullah (Jurusan Tadris Bahasa Indonesia, 2022)
The phenomenon of using language on the internet is something unique. This study aims to describe the influence of gender on the variety of languages in Instagram captions and realize the intended meaning. This study uses a Computer-Mediated Discourse Analysis (CMDA) approach. The data collection technique is in the form of screenshots containing captions with the theme of make-up on Instagram social media. Data analysis in this study refers to Lakoff's theory of female language characteristics and Mulac's theory of male language characteristics. The results of the analysis show that the variety of languages used by men and women in Instagram captions have some similarities in the use of language features and also vary in realizing their intentions. This study recommends that sociolinguistics is an interesting topic for research so that future fields of study pay more attention to the rapidly changing phenomena in social media.Fenomena penggunaan bahasa di internet merupakan sesuatu yang khas. Penelitian ini bertujuan untuk mendeskripsikan pengaruh gender terhadap ragam bahasa pada caption Instagram dan merealisasikan makna yang dimaksud. Penelitian ini menggunakan pendekatan Computer Mediated Discourse Analysis (CMDA). Teknik pengumpulan data berupa tangkapan layar yang memuat caption yang bertemakan make-up dalam sosial media Instagram. Analisis data dalam penelitian ini mengacu pada Teori Lakoff tentang karakteristik bahasa perempuan dan Teori Mulac tentang karakteristik bahasa laki-laki. Hasil analisis menunjukkan bahwa ragam bahasa yang digunakan oleh laki-laki dan perempuan pada caption Instagram memiliki beberapa kesamaan dalam penggunaan fitur bahasa dan beragam pula dalam merealisasikan maksudnya. Studi ini merekomendasikan bahwa sosiolinguistik merupakan topik yang menarik untuk diteliti sehingga bidang studi kedepannya lebih memperhatikan fenomena yang berubah dengan cepat di media sosial.